THU0095 CIGARETTE SMOKING AS PREDICTOR OF INADEQUATE RESPONSE TO METHOTREXATE IN RHEUMATOID ARTHRITISPATIENTS NAÏVE TO DMARDS. (June 2019) - Perra, Daniela; Cangemi, Ignazio; Congia, Mattia; Bartocci, Marco; Chessa, Elisabetta; Dessì, Martina; Mascia, Piero; Pau, Andrea; Pilia, Josephine; Platè, Ilaria; Renzullo, Francesco Luca; Floris, Alberto; et al.
Abstract : Background: Methotrexate (MTX) is the gold standard as first line treatment in rheumatoid arthritis (RA). Identifying predictors of response to MTX should be crucial in the view of a personalized therapy. Objectives: To identify prevalence and potential clinical baseline predictors of inadequate response (IR) to MTX in RA patients naïve to disease modifying anti-rheumatic drugs (DMARDs)*. Methods: Data of 233 consecutive RA patients (according to ACR/EULAR 2010 criteria) naïve to traditional and biologic DMARDs, attending the AOU University Clinic, Rheumatology Unit, Monserrato (Cagliari), Italy, were analyzed. Table 1 shows baseline demographic, clinical and serological characteristics of the cohort. Patients failing to reach low disease activity state (DAS 28 > 3.2) at 6 months (T1) since the beginning of MTX (T0) or patients undergoing therapeutic modification for persistently high disease activity (switch or addition of other traditional or biological DMARDs) before T1 were considered as IR. By univariate analysis, demographic, clinical and serological factors recorded at T0 were evaluated as potential predictors of IR at T1. Afterwards, factors with p<0.10 were included in a logistic regression model, to identify independently associated factors to IR (p <0.05). Odd-Ratio (OR) with 95% confidence interval (CI) was calculated. Results: At T1, 104 patients (44.6%) were classified as IR to MTX. In univariate analysis, factors significantly associated with IR were: female gender (69.2% vs. 54.3%; p=0.02), condition of "current smoker" (22.1% vs. 10.9%; p=0.012), ESR [median (IQR): 30.0 (19.0-48.0) vs. 40.0 (25-62); p=0.035] and DAS28 (mean ± standard deviation: 5.5 ± 1.1 vs. 5.2 ± 1.3; p=0.037). High-titre positivity for RF and/or ACPA (57.3% vs. 45.9%; p=0.095) and high cumulative steroids dose [852 mg (300-1200) vs. 691 mg (0-150); p=0.071] were numerically higher in IR. In multivariate analysis, the "current smoker" condition was confirmed as the only independent factor associated with IR to MTX after 6 months of treatment (OR: 2.333, 95% CI: 1.132-4.805; p=0.022). No significant association between ex-smoker status and IR to MTX was demonstrated. This result was confirmed even after stratification of ex-smokers over the time since smoking stop. Finally, for both current smokers and ex-smokers, the duration of exposure to cigarette smoking did not show any significant association with IR. Conclusion: In this RA cohort, the condition of "current smoker" was the only predictor of IR to MTX. This observation, together with the lack of association between previous smoking habit and IR to MTX, further prompt to recommend cessation of cigarette smoking in patients with RA who begin treatment with MTX. Acknowledgement: This study was supported by an unconditioned Research grant from Pfizer Inc. Disclosure of Interests: None declared